Imidazolium-based ionic liquid-catalyzed hydrosilylation of imines and reductive amination of aldehydes using hydrosilane as the reductant. Issue 51 (21st June 2017) - Li, Bin; Zhang, Shilin; Wu, Weizhen; Liang, Lecheng; Jiang, Shaohua; Chen, Lu; Li, Yibiao
Abstract : Efficient imidazolium-based ionic liquid-catalyzed hydrosilylation of imines and reductive amination using a catalytic amount of [BMIm][FeCl4 ]. Abstract : The first imidazolium-based ionic liquid-catalyzed hydrosilylation of imine and reductive amination of aldehydes with primary amines using a catalytic amount of 1-butyl-3-methylimidazolium tetrachloride iron [BMIm][FeCl4 ] and Ph2 SiH2 as a reductant were performed under mild conditions. Good yields of secondary amines with high chemoselectivity and a tolerance for a wide range of functional groups were obtained.